INFLUENCE OF ENVIRONMENTAL QUALITY FOR SUSTAINABLE DEVELOPMENT IN INDONESIA - Rahayu, Heffi Christya; Handri, Handri (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2023)
Global warming and environmental damage are important issues today. Sustainable development must pay attention to the impact of social and economic actions on the environment. To find out the quality of the environment is influenced by what factors in Indonesia. It is necessary to conduct research using model regression analysis of panel data with variables of GRDP, poverty, energy consumption, and HDI against IKLH there are 33 provinces in Indonesia. The results of the model selected and will be used in this study is the Fixed Effect Model. From the results of the partial analysis, it is known that poverty and HDI have a significant influence on environmental quality, where both variables have a positive effect on IKLH. Meanwhile, GRDP and Energy Consumption do not have a significant influence on IKLH. Simultaneously, the four independent variables affect IKLH as a dependent variable. The magnitude of the influence of the four independent variables (HDI, Poverty, GRDP, and Energy Consumption) on IKLH is 80.95%, and the remaining 19.05% is a variable that is not used in the study